Harnessing the power of machine learning for crop improvement and sustainable production - Khatibi, Seyed Mahdi Hosseiniyan; Ali, Jauhar (Frontiers in Plant Science, 2024)
Crop improvement and production domains encounter large amounts of expanding data with multi-layer complexity that forces researchers to use machine-learning approaches to establish predictive and informative models to understand the sophisticated mechanisms underlying these processes. All machinelearning approaches aim to fit models to target data; nevertheless, it should be noted that a wide range of specialized methods might initially appear confusing. The principle objective of this study is to offer researchers an explicit introduction to some of the essential machine-learning approaches and their applications, comprising the most modern and utilized methods that have gained widespread adoption in crop improvement or similar domains. This article explicitly explains how different machine-learning methods could be applied for given agricultural data, highlights newly emerging techniques for machinelearning users, and lays out technical strategies for agri/crop research practitioners and researchers.